PEMANFAATAN APLIKASI SIANDINI SEBAGAI ALAT PEMANTAUAN DAN PENGENDALIAN INFLASI HARGA BAHAN KEBUTUHAN POKOK DAN BAHAN PENTING OLEH PEMERINTAH DAERAH KABUPATEN SUMBAWA - Saleh, Muhammad; Ary Busman, Sherwin (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2020)
This study discusses the use of public service innovationsby the Sumbawa Regency Regional Inflation Control Team (TPID) in an effortfacilitate the process of monitoring and making policy on material price inflationbasic needs and essential needs in the district of Sumbawa. This innovation is given a nameSIANDINI (Inflation Early Warning Information System) which is an application in the fieldgovernance and public services that process realtime price info on the wholesale markettraditional and modern markets in Sumbawa Regency along with analysis and recommendationsfor Local Government, Community, and Private sector. The purpose of this study is toknow the results and description of the use of the SIANDINI application in an effortpolicy making that remains effective and right on target. This research usestype of qualitative research methods - descriptive using the collection techniqueinterview data, observation and documentation. Results of the SIANDINI application researchsucceeded in producing achievements, namely providing ease of use of the application tousers, namely the government and society, so the use of the SIANDINI applicationhelp provide information on prices of basic necessities to the public and asdecision support tool for controlling inflation by the government.